Pendampingan Renovasi Plafond dan Pembuatan Tirai Pembatas Posyandu Mekar Kuntum Bau Semerbak Kelurahan Kampung Baru Kota Pekanbaru - Muthia Anggraini; Alfian Saleh; Virgo Trisep Haris (Universitas Semarang, 2023)
Kampung Baru Village is one of the villages in Senapelan District, Pekanbaru City. Has a Posyandu Mekar Kuntum Smell Fragrant. Posyandu functions are explained by partners for continuous monitoring of public health. Currently, posyandu still has simple facilities and infrastructure. To encourage people to feel comfortable when they are there, it is necessary to add facilities and infrastructure, namely by installing ceilings and dividing curtains. The purpose of this community service is to assist partners in making planning designs and cost budget plans (RAB) for ceiling renovations and curtain installation. The method used is the counseling method. The output of this activity is a planning drawing and the type of ceiling and curtain used and the RAB for installing the ceiling and curtain. The installed ceiling is a type of gypsum with a volume of 45 m2. For blinds that are installed made of soft and not transparent. Assisting with the installation of the posyandu ceiling and curtain.